The Muslim Religiosity-Personality Inventory (MRPI): towards understanding differences in the Islamic religiosity among the Malaysian youth - Krauss, Steven Eric; Hamzah, Azimi; Juhari, Rumaya; Abdul Hamid, Jamaliah (Universiti Putra Malaysia Press, 2005)
As Malaysia continues towards its goal of Vision 2020, the youth of today move closer to becoming the first leaders of a fully developed Malaysia. Currently, however, youth's - the Muslim youth in particular - lifestyles are changing and there is great concern over the socially precarious behaviours in which many young people are engaging. Though Islam and its rich history are evidence of the efficacy of religion in upwardly transforming human beings in any time or place, the current prevalence of a variety of social problems among Muslims has raised many questions in relation to the Islamic understanding and practice. As such, there is an urgent need to understand and assess the key areas of the religious commitment among the youth - also known as religiosity - and begin to explore in the what ways it might act in as an asset within the nation building process. In response to this need, the Institute for Community and Peace Studies (PEKKA) at UPM, along with the researchers from UKM, undertook a two-and-a-half year IRPA initiative to develop the religiosity 'norms' for selected groups of Malaysian Muslim youth as a first step toward understanding their religiosity in a broader context. Overall, the three-phase initiative aimed to: 1) define religiosity from the Islamic perspective; 2) develop a measurement instrument for assessing Islamic religiosity; and 3) obtain religiosity normed scores for the selected groups of Muslim youth. The current paper presents the Islamic religiosity model and instrument constructs, along with some initial findings that indicate relatively higher scores by the respondents on the Islamic Worldwide construct (Islamic understanding) than on the Religious Personality construct (application of Islamic teachings in everyday life). This research ultimately aims to inform policy makers and practitioners at all levels of youth work with the goal of developing interventions to enhance the aspects of the youth religiosity.